Analisis Bimbingan Keagamaan Berbasis Pesantren Terhadap Narapidana Penyalahgunaan Narkoba Di Lembaga Pemasyarakatan Kelas II A Banyuwangi - Khomariyah, Dianatul; Yohandi; Sulaiman, A. Husam (CV. SINAR HOWUHOWU, 2025)
Drug abuse among inmates causes not only legal problems but also psychological, social, and spiritual deterioration. Therefore, rehabilitation efforts need to be transformative and restorative. This study examines the implementation and impact of pesantren-based religious guidance on drug-abusing inmates in correctional institutions. Using a qualitative case study approach, data were collected through in-depth interviews, observations, and document analysis involving inmates, religious mentors, and correctional officers. The findings show that pesantren-based guidance is implemented through congregational prayers, Quran recitation, Islamic studies, religious lectures, and moral habituation. These activities contribute to positive changes in inmates’ behavior and attitudes, including increased religious awareness, emotional stability, inner peace, and motivation to stop drug abuse. Additionally, improvements in discipline and rule compliance were observed. Thus, pesantren-based religious guidance is an effective model for spiritual and social rehabilitation of drug-abusing inmates.